Political mandate on the collection of zakat profession by government officers in Madura - Choiri Muttaqin; Maadi Alam Suud; Nurfadila Yeni (BIO Web of Conferences)
Ecosystems and good management are needed to make a superior tourist destination, so that later it will lead to the welfare of the community and micro, small and medium enterprises around it. Therefore, an Entrepreneurial Ecosystem policy is needed to develop a superior tourist destination and can improve the economy of the community and small and medium enterprises. The purpose of this study is to identify the Entrepreneurial Ecosystem tourism policy model in increasing the potential and welfare of micro, small and medium enterprises in Pamekasan. This research is descriptive qualitative in nature. The research location was determined purposively, namely in Pamekasan Regency. Primary data sources were obtained directly from the research subjects, in this case the parties related to the village-owned enterprises of tourism objects, namely: Tourism managers, related agencies, the Office of Micro, Small and Medium Enterprises Cooperatives and stakeholders. The results of this study indicate that the appropriate policy model is the Political System model which places the policy as the output of the system. This policy model is oriented towards community interest inputs, in this case tourism stakeholders both private and government that support the Entrepreneurial Ecosystem. This research also shows that the entrepreneurial ecosystem is still not well developed in Pamekasan because stakeholders from both the private sector and the government have not synergised to grow and motivate the entrepreneurial ecosystem. Thus, the tourism entrepreneurial ecosystem policy model still needs to be revised and improved in Pamekasan.